2010
DOI: 10.5194/angeo-28-1333-2010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relation between PMSE and ice mass density

Abstract: Abstract. Radar reflectivities associated with Polar Mesosphere Summer Echoes (PMSE) are compared with measurements of ice mass density in the mesopause region. The 54.5 MHz radar Moveable Atmospheric Radar for Antarctica (MARA), located at the Wasa/Aboa station in Antarctica (73 • S, 13 • W) provided PMSE measurements in December 2007 and January 2008. Ice mass density was measured by the Solar Occultation for Ice Experiment (SOFIE). The radar operated continuously during this period but only measurements clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Unlike SNR, the radar volume reflectivity is an intrinsic characteristics of PMSE strength which can be used for comparison of PMSE measured with different radars at different locations. An additional advantage of using η is in the fact that its value should be directly related to physical parameters such as electron and ice particle density, static stability and turbulence characteristics (Kirkwood et al, 2010b;Varney et al, 2010). Nowadays estimations of PMSE reflectivity have been made using a number of MesosphereStratosphere-Troposphere (MST) radars located both in the northern and southern polar regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SNR, the radar volume reflectivity is an intrinsic characteristics of PMSE strength which can be used for comparison of PMSE measured with different radars at different locations. An additional advantage of using η is in the fact that its value should be directly related to physical parameters such as electron and ice particle density, static stability and turbulence characteristics (Kirkwood et al, 2010b;Varney et al, 2010). Nowadays estimations of PMSE reflectivity have been made using a number of MesosphereStratosphere-Troposphere (MST) radars located both in the northern and southern polar regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…But the observed (weak) correlation is at least consistent with our hypothesis. Empirically it has been found that PMSE reflectivity increases roughly in proportion to electron density, at least for low levels of geomagnetic disturbance (K P < 3) at Wasa (Kirkwood et al, 2010b), and we can expect electron density due to ionisation of NO by solar Lyman-α to increase as [NO] 0.5 . Taking the comparison a step further, the black line in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Geophys., 31, 333-347, 2013 www.ann-geophys.net/31/333/2013/ twice as much ice mass in the 03:00-05:00 LT time sector compared to the 10:00-24:00 LT sector. However, according to the results of Kirkwood et al (2010b), relating ice-mass and electron densities to PMSE reflectivities, this should lead to a factor of only 2 difference between PMSE reflectivities between 03:00-05:00 LT and those at corresponding solar zenith angles in the afternoon (19:00-21:00 LT) if solar EUV is the only source of ionisation. Since the observed difference in reflectivities is an order of magnitude, it seems likely that this site is affected by energetic particle precipitation in the early morning even when K indices suggest that the situation is quiet.…”
Section: Pmse Response To Magnetic Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…Some are associated with noctilucent clouds (NLCs), and it is widely accepted that PMSEs are a consequence of the existence of icy "dust" particles in the vicinity of the polar summer mesopause (e.g. Kirkwood et al, 2010). Havnes et al (1996) first reported the detection of charged PMSE dust particles with a rocket-borne probe launched in an effort to establish the relationship between the PMSE signals and the charge carried by dust.…”
Section: Introductionmentioning
confidence: 99%